1999
DOI: 10.1021/ja991949s
|View full text |Cite
|
Sign up to set email alerts
|

Conformational and Thermodynamic Properties of Parallel Intramolecular Triple Helices Containing a DNA, RNA, or 2‘-OMeDNA Third Strand

Abstract: The thermodynamic stability and solution conformational properties of three intramolecular triple helices based on the sequence AGAAGA-x-TCTTCT-x-TCTTCT (x is a non-nucleotide linker) comprising a DNA duplex and DNA, RNA, or 2‘-OMeDNA third strands have been compared. The most stable triple helix contains the 2‘-OMe third strand, followed by the triplex containing RNA in the third strand. Comparison of the NMR spectroscopic data for the RNA hybrid triplex with those of the all-DNA triplex shows that the duplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 29 publications
5
47
0
Order By: Relevance
“…Recent analyses by NMR and FT-IR have shown that D:DD and R:DD triple helices (where DD stands for the DNA double helix, and D: or R: for the DNA or RNA TFO, respectively) have heterogeneous backbone conformations, leading to energetically compromised conformations for certain ribo-and deoxyribonucleotides in the three strands (9 -15). Thermodynamic studies have shown that R:DD triple helices have higher thermal stability than D:DD ones (8,(15)(16)(17)(18), whereas similar free energies and equilibrium constants have been found by isothermal titration calorimetry and EDTA cleavage (19,20). Results in our laboratory and others, with third strand sequences containing a variable number of nucleotides with modified bases or backbones, show thus far nonunderstood differences in affinity as a function of the target sequence and the position of the modified nucleosides in the chain (21)(22)(23).…”
supporting
confidence: 58%
“…Recent analyses by NMR and FT-IR have shown that D:DD and R:DD triple helices (where DD stands for the DNA double helix, and D: or R: for the DNA or RNA TFO, respectively) have heterogeneous backbone conformations, leading to energetically compromised conformations for certain ribo-and deoxyribonucleotides in the three strands (9 -15). Thermodynamic studies have shown that R:DD triple helices have higher thermal stability than D:DD ones (8,(15)(16)(17)(18), whereas similar free energies and equilibrium constants have been found by isothermal titration calorimetry and EDTA cleavage (19,20). Results in our laboratory and others, with third strand sequences containing a variable number of nucleotides with modified bases or backbones, show thus far nonunderstood differences in affinity as a function of the target sequence and the position of the modified nucleosides in the chain (21)(22)(23).…”
supporting
confidence: 58%
“…Structural studies indicate that this modification stabilizes the C3Ј-endo,2Ј-exo configuration of the sugar. This is the optimal conformation for triplex formation by pyrimidine oligonucleotides, and provokes the least perturbation of the underlying duplex (31).…”
mentioning
confidence: 99%
“…First, the stability of TFO against nucleases is a concern, which is universal for all ODN-based technologies. Triplex formation involves conformational changes on TFO sequence and some distortion of the underlying dsDNA (312,313), which leads to the intrinsic instability of triplex structures. Triplex formation with (C, T)-motif TFOs is pH dependent because cytosines must be protonated at the N3 position in slightly acidic media (pH<6) to form two hydrogen bonds with G (314).…”
Section: Rules For Triplex Formationmentioning
confidence: 99%
“…The beneficial effects are probably due to the shift in the conformational equilibrium of the sugar to C3' endo configuration. This conformation imposes minimal distortion on the underlying duplex (313) and thus provide "pre-organization", which has entropic benefits (344). In 2'-O-aminoethyl (2'-AE) modification, both a positive charge and a "pre-organized" sugar conformation can be provided (343).…”
Section: Chemical Modifications On Tfosmentioning
confidence: 99%